(untitled) (Research, Society and Development, 2021)
Mango agribusiness is an expanding activity in Brazil and produces a large volume of waste that are not reused. Mango seeds are one of the residues from fruit processing, and are a potential starch source. In the food industry, starch is used as a functional ingredient, allowing the preservation of important characteristics of foods. The objectives of this study were to extract starch from mango seed, and to characterize it in terms of its physicochemical, technological and rheological properties. Starch extraction involved washing, cutting, and milling the mango seeds. The extraction yield was 53.89% and the starch granules presented spherical to irregular ellipsoidal shapes with superficial grooves and average size of 20 µm. It had an initial paste temperature of 75.3 °C and a maximum viscosity of 706 BU at 88.1 ºC. The rate of syneresis, 1.51%, was considered low, which indicates a starch with good stability at low temperatures. In the texture profile it was found that there was a significant difference (p ≤ 0.05) in the texture profile of gels with sodium chloride, sucrose and citric acid added. The gel with emulsifier showed no significant difference in any of the parameters analyzed (hardness, cohesiveness and gumminess). The properties of the starch indicated great potential for use in food products.